KORPORACJE TRANSNARODOWE W PROCESIE GLOBALIZACJI - Jantoń-Drozdowska, Elżbieta (Wydział Prawa i Administracji UAM, 2006)
The aim of this paper is to show the significance for economic globalisation of the expansion of transnational corporations (TNCs) by means of foreign direct investment. Factors conducive to globalisation are directly linked to the liberalisation of international trade, the policy adopted by individual states towards transnational corporations, and also with growing competition in the world market. The author presents other specific factors stimulating globalisation, both in the production and the financial sphere. Their combined result is an increase in the importance of transnational corporations which grow in numbers production output, as well as sales, assets, employment abroad or exports. As a consequence there is a rise, measured by the transnationalisation index, in the level of globalisation of host economies and of TNCs themselves.
TRANSNATIONAL CORPORATIONS IN THE GLOBALISATION PROCESS